Stability of Nonlinear Systems of Fractional Order Differential Equations (Baghdad Science Journal, 2025)
In this paper, a sufficient condition for stability of a system of nonlinear multi-fractional order differential equations on a finite time interval with an illustrative example, has been presented to demonstrate our result. Also, an idea to extend our result on such system on an infinite time interval is suggested.